2014
DOI: 10.1097/pcc.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Pediatric Cardiac Extracorporeal Life Support Survivors*

Abstract: Pediatric cardiac extracorporeal life support survivors showed lower health-related quality of life than healthy children, children with chronic conditions, and children with congenital heart disease who did not receive extracorporeal life support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In 51 cardiac patients having E-CPR, the CPTFP reported 49% survival to hospital discharge, 43% survival to 5 years, full-scale intelligence quotient of survivors 76.5 (SD 15.9), GAC of 74.5 (SD 20.3) with 47% having a score below 2 SD of the population mean, and 24% having both full-scale intelligence quotient and GAC below 2 SD of the population mean, similar findings to those of all cardiac ECMO cases in the 10-year review [19]. When the CPTFP examined health-related quality of life, this was lower in cardiac ECMO survivors than in other children with CHD having surgery in early infancy; whether cannulation was from the operating room or done in the PCICU was not associated with this outcome [20]. Finally, of 502 CPTFP patients having cardiac surgery early in infancy, ECMO was an independent predictor of mortality at 4.5 years (hazard ratio 1.93, 95% CI 1.17, 3.18, p  = 0.010) and of neurocognitive outcome, with an effect size for full-scale intelligence quotient of − 13.6 (95% CI − 21.3, − 5.9, p  = 0.001) and for GAC of − 12.7 (95% CI − 20.3, − 5.0, p  = 0.001) [21].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In 51 cardiac patients having E-CPR, the CPTFP reported 49% survival to hospital discharge, 43% survival to 5 years, full-scale intelligence quotient of survivors 76.5 (SD 15.9), GAC of 74.5 (SD 20.3) with 47% having a score below 2 SD of the population mean, and 24% having both full-scale intelligence quotient and GAC below 2 SD of the population mean, similar findings to those of all cardiac ECMO cases in the 10-year review [19]. When the CPTFP examined health-related quality of life, this was lower in cardiac ECMO survivors than in other children with CHD having surgery in early infancy; whether cannulation was from the operating room or done in the PCICU was not associated with this outcome [20]. Finally, of 502 CPTFP patients having cardiac surgery early in infancy, ECMO was an independent predictor of mortality at 4.5 years (hazard ratio 1.93, 95% CI 1.17, 3.18, p  = 0.010) and of neurocognitive outcome, with an effect size for full-scale intelligence quotient of − 13.6 (95% CI − 21.3, − 5.9, p  = 0.001) and for GAC of − 12.7 (95% CI − 20.3, − 5.0, p  = 0.001) [21].…”
Section: Discussionmentioning
confidence: 53%
“…Third, those patients having early ECMO are a high-risk group for mortality and poor functional outcomes. We have previously described that ECMO is a risk factor for adverse neurocognitive and health-related quality of life outcomes [20, 21]. These children warrant neurodevelopmental follow-up in order to identify adverse outcomes and provide early intervention in order to optimize each patient’s achievement of his/her full potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the 8 studies that evaluated patients who required ECMO support for acquired or congenital heart disease, patients were diverse in age and disease presentations (i.e., cyanotic and non-cyanotic congenital heart disease or acquired heart disease from myocarditis or cardiomyopathy) (22, 4548, 50, 51). Three studies used the PCPC and Pediatric Overall Performance Category (POPC) to determine outcomes either at discharge or within 3 years of discharge and showed that 81%-91% were favorable, based on PCPC/POPC <3 or <4 or no change from baseline (46, 47, 50).…”
Section: Resultsmentioning
confidence: 99%
“…More detailed evaluations that included neuropsychological testing revealed that, at 1 to 5 years after discharge, 25% to 50% of those seen in follow-up tested in the severely disabled range, defined as more than 2 SD below the mean for the population on the given test (i.e., WPPSI, WISC, BSID) (16, 22, 51). Studies that evaluated quality of life showed that 34% to 53% of cardiac ECMO survivors reported significantly diminished quality of life compared to age-matched, healthy peers (45, 48). One of two studies showed that quality of life was also significantly diminished compared to that of peers with cardiac disease but no history of ECMO (48).…”
Section: Resultsmentioning
confidence: 99%
“…Do we do a telephone interview or examine the patient? Long-term outcomes have been part of neonatal and paediatric care for many years and outcomes are well known [ 36 , 37 ]. Unfortunately, they reflect treatment protocols that no longer exist and have changed.…”
Section: Reviewmentioning
confidence: 99%